Intermittent hypoxia does not affect endurance performance at moderate altitude in well-trained athletes - Faulhaber, M.; Gatterer, H.; Haider, T.; Patterson, C.; Burtscher, M. (Journal of Sports Sciences, 2010)
In this study, we examined the effects of a pre-acclimatization programme on endurance performance at moderate altitude using a resting intermittent hypoxia protocol. The time-trial performance of 11 cyclists was determined at low altitude (600 m). Athletes were randomly assigned in a double-blind fashion to the hypoxia or the control group. The pre-acclimatization programme consisted of seven sessions each lasting 1 h in normobaric hypoxia (inspired fraction of oxygen of 12.5 %, equivalent to approximately 4500 m) for the hypoxia group (n = 6) and in normoxia (inspired fraction of oxygen of 20.9 %) for the control group (n = 5). The time-trials were repeated at moderate altitude (1970 m). Mean power output during the time-trial at moderate altitude was decreased in the hypoxia group (-0.26 ± 0.11 W/kg) and in the control group (-0.13 ± 0.04 W/kg) compared with at low altitude but did not differ between groups (P = 0.13). Our results suggest that the applied protocol of intermittent hypoxia had no positive effect on endurance performance at moderate altitude. Whether different intermittent hypoxia protocols are advantageous remains to be determined.